Assessing rural tourism development in Semporna, Sabah, Malaysia - Chia, Kei Wei; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (2012)
Tourism is perceived as ‘white knight’ to save the economics of a particular place. Specifically, rural tourism has been perceived as panacea for social ills & economic of the countryside as it is often used to improve the local’s livelihood by generating job opportunities and income. However, inappropriate rural tourism development may lead to several negative impacts. This paper aims to identify the challenges experience in Semporna district and explores the existence of sustainable indicators in the development of rural tourism sector at a costal destination and the applicability of the indicators. Data were collected via interview, personal communication and secondary data. The findings demonstrate some challenges experience in Semporna district result from tourism development. It was found that Semporna fulfill majority of the indicators suggested by UNWTO.